2008
DOI: 10.1099/ijs.0.65394-0
|View full text |Cite
|
Sign up to set email alerts
|

Methanolinea tarda gen. nov., sp. nov., a methane-producing archaeon isolated from a methanogenic digester sludge

Abstract: Methanolinea tarda gen. nov., sp. nov., a methaneproducing archaeon isolated from a methanogenic digester sludge A novel methane-producing archaeon, strain NOBI-1 T was isolated from an anaerobic, propionate-degradation enrichment culture, which was originally obtained from a mesophilic methanogenic sludge digesting municipal sewage sludge. Cells were non-motile, rod-shaped, 0.7-1.0 mm by 2.0 mm, and formed multicellular filaments longer than 8 mm. Growth was observed between 35 and 55 6C (optimum 50 6C) and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(75 citation statements)
references
References 43 publications
6
68
0
1
Order By: Relevance
“…Using the 16S rRNA gene and McrA gene as biomarkers, temperature-dependent variations were also observed with acetoclastic methanogen populations found in the order Methanosarcinales (Supplementary Figure 4). The hydrogenotrophic methanogens identified here are closely related to methanogens found in mesophilic and thermophilic TA-degrading reactors (Wu et al, 2001;Chen et al, 2004), and together with Methanolinea tarda NOBI-1 recently isolated from anaerobic digestion processes (Imachi et al, 2008), form a novel cluster separate from other known hydrogenotrophic methanogens. The comparison of McrA genes further suggests that the methanogens found in the new cluster are likely different from M. tarda NOBI-1 (Supplementary Figure 4B). )…”
Section: S Rrna-based Community Profilingmentioning
confidence: 92%
See 1 more Smart Citation
“…Using the 16S rRNA gene and McrA gene as biomarkers, temperature-dependent variations were also observed with acetoclastic methanogen populations found in the order Methanosarcinales (Supplementary Figure 4). The hydrogenotrophic methanogens identified here are closely related to methanogens found in mesophilic and thermophilic TA-degrading reactors (Wu et al, 2001;Chen et al, 2004), and together with Methanolinea tarda NOBI-1 recently isolated from anaerobic digestion processes (Imachi et al, 2008), form a novel cluster separate from other known hydrogenotrophic methanogens. The comparison of McrA genes further suggests that the methanogens found in the new cluster are likely different from M. tarda NOBI-1 (Supplementary Figure 4B). )…”
Section: S Rrna-based Community Profilingmentioning
confidence: 92%
“…Several studies (Chan, 2000;Qiu et al, 2006;Imachi et al, 2008) have observed the existence of multiple bacterial populations in highly enriched methanogenic cultures degrading carbon substrates like formate, acetate, propionate and phthalate isomers. These observations were shown through a defined mixed culture (Dolfing et al, 2008), suggesting that syntrophic interactions in methanogenic enrichments are more complex than simple pairwise syntroph-methanogen relationships.…”
Section: Methanogenic Syntrophymentioning
confidence: 99%
“…In mesophilic reactors 1, 2, 4 and 6, the presence of Methanomicrobiales-related methanogens (MG1200m) was observed (Table 4), but their detailed phylogenetic affiliations within this family could not be properly identified using subfamily-, genus-and speciesspecific probes (Table 3), because major members of the order Methanomicrobiales in reactors 1 and 2 were related to uncultured environmental clones and a novel methanogen (Methanoline tarda) isolated and characterized very recently (Imachi et al, 2008) (Figure 3). Thus, additional scissor probes are needed to account for the presence of these yet-to-beidentified taxa.…”
Section: Discussionmentioning
confidence: 99%
“…We, therefore, changed our strategy to isolation based on the co-culture technique in which an H 2 -producing bacterium and its substrate were co-inoculated together with the original sample in the primary enrichment and in further passages to fresh medium, so that H 2 was supplied to methanogens constantly at very low concentrations (,100 Pa). The underlying idea has been described in our previous reports (Sakai et al, 2007;Imachi et al, 2008). The method has been proven to be successful to eliminate non-target fast-growing methanogenic populations.…”
mentioning
confidence: 99%